The Analgesic Effect and Toxicity of Red and White Ginger on Mus Musculus with the Acetate Writhing Test - Dewi, Vonny Khresna; Barkinah, Tut; Kirana, Rita; Rizki, Muhammad Ikhwan (Medical Laboratory Technology Journal, 2024)
Based on data from the World Health Organization in 2020, the incidence of dysmenorrhea was 1,769,425 (90%) women who suffered from dysmenorrhea, with 10-16% suffering from severe dysmenorrhea. The problem of pain is very disruptive to activities, so prevention and treatment of pain must be a concern. Ginger is a natural ingredient that grows in South Kalimantan and is empirically used to treat pain. The study aimed to determine the analgesic effects and toxicity of red and white ginger from Banjarmasin and Banjar Regency. The nutrient content profile of the soil where the ginger grew was analyzed, and it was determined by nitrogen content, cation exchange capacity, and soil pH. The content of active compound groups was analyzed using specific reagents to determine the presence of active compounds. Determination of total phenolic levels using a colorimetric method using a UV-Vis spectrophotometer. The instant ginger formula was optimized with organoleptic test result parameters. Acute toxicity tests using male Wistar rats with observations for 14 days. Analgesic tests were conducted on Mus musculus using the acetic acid writhing test. The results showed that the highest nitrogen (1,34%), cation exchange capacity (29.22 me/100 g), and soil pH levels (6,89) were in the soil where the ginger samples from Banjar Regency grew. The chemical compound content in all gingers contained the same phenolics, flavonoids, tannins, saponins, and terpenoids. The levels of marker compounds in succession from Banjarmasin red ginger, Banjarmasin white ginger, Banjar Regency red ginger, and Banjar Regency white ginger were 7.43%, 6.26%, 8.52%, and 7.12%, respectively. The results of formula optimization showed that all gingers had a sweet and spicy taste, a distinctive odor, powder form, and a reddish-brown color in red ginger and pale yellow in white ginger. The toxicity test results showed that at doses of 300 mg/Kg BW and 2000 mg/Kg BW, there was no toxic effect on the administration of ginger extract. Analgesic activity showed that all gingers had an analgesic effect at a dose of 200 mg/Kg BW. The analgesic effects from the strongest to the lowest were red ginger from Banjar Regency, red ginger from Banjarmasin, white ginger from Banjar Regency, and white ginger from Banjarmasin. This study concludes that red ginger from Banjar Regency has the most potent analgesic activity and no toxicity for all ginger.